(untitled) (Economics and region, 2019)
As a result of processes of globalization and European integration of national equity markets methodological approaches to the process of corporate governance are changing in economic science. They are gradually being transformed in accordance with the new challenges of international laws, standards and trends. The mentioned processes affected the functioning primarily of large public domestic joint-stock companies and international corporations, who want to raise capital on international stock exchanges. Creating effective corporate governance systems based on corporate social responsibility always contributes to the confidence of strategic and portfolio investors, stock markets and all interested parties. Therefore, the study of the problem of improving corporate governance in a globalizing environment should be considered as an important tool not only for capital markets, but also for a sustainable institution of responsible corporate governance and the growth of business value in the long run. The purpose of the article is to study the corporate governance system in joint-stock companies in the context of the implementation of international ISO standards and changes in the current legislation.